Inclusione 3.0 - Giaconi, Catia (Traiettorie inclusive - Open Access, 2019)
The curators, on the occasion of the World Day of Disability, have gathered together contributions, reflections, projects and workshops presented to offer an interdisciplinary reflection on the theme of disability and inclusion, beginning with "Unimc for Inclusion", a week rich in meetings on the theme of inclusion held at the University of Macerata. The authoritative contributions of scholars from diverse disciplinary fields, allow readers to retrace the theme of inclusion from different theoretical research perspectives, reconstructing an interesting corollary of reflections and operational paths ranging from special pedagogy, general pedagogy, psychology, social robotics, virtual reality, economics, law, literature, philosophy, art, etc. It is due of this approach that the text is particularly pertinent to teachers, educators and pedagogues in active service and in training, not least because of the range of workshop proposals and transferable experiences in school contexts and in day and residential centres.